2004
DOI: 10.1002/hbm.20076
|View full text |Cite
|
Sign up to set email alerts
|

Formal characterization and extension of the linearized diffusion tensor model

Abstract: We analyzed the properties of the logarithm of the Rician distribution leading to a full characterization of the probability law of the errors in the linearized diffusion tensor model. An almost complete lack of bias, a simple relation between the variance and the signal-to-noise ratio in the original complex data, and a close approximation to normality facilitated estimation of the tensor components by an iterative weighted least squares algorithm. The theory of the linear model has also been used to derive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
177
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(180 citation statements)
references
References 17 publications
2
177
0
1
Order By: Relevance
“…Susceptibility-induced geometric distortion was corrected using a 1-D correction algorithm (motion correction was also employed as part of this routine) along the phase-encoding direction with the separatelyacquired field map (Jezzard and Balaban, 1995). The software used a weighted linear least square method to calculate FA maps (Salvador et al, 2005). Intracranial voxels were separated out using a brain extraction tool-generated brain mask.…”
Section: Analysis Of Imagesmentioning
confidence: 99%
“…Susceptibility-induced geometric distortion was corrected using a 1-D correction algorithm (motion correction was also employed as part of this routine) along the phase-encoding direction with the separatelyacquired field map (Jezzard and Balaban, 1995). The software used a weighted linear least square method to calculate FA maps (Salvador et al, 2005). Intracranial voxels were separated out using a brain extraction tool-generated brain mask.…”
Section: Analysis Of Imagesmentioning
confidence: 99%
“…It is well known that the noise in MRI can be described accurately by a Rician distribution Salvador et al (2005). Salvador et al (2005) showed that the error distribution conforms closely to a normal distribution with a zero-mean and standard deviation equal to the inverse of the signal-to-noise ratio (SNR), i.e.…”
Section: Observation Densitymentioning
confidence: 99%
“…Here, we simply set tr(D) to be the trace of the diffusion tensor D estimated using the linear least squares estimation (Basser et al, 1994), and set λ ⊥ = (λ 2 + λ 3 )/2. The SNR is estimated using the weighted least squares method in (Salvador et al, 2005). Panels (a) and (c) of Fig.…”
Section: Observation Densitymentioning
confidence: 99%
“…Jones et al [12] presented an estimation method that incorporates noise level estimation. Salvador et al [18] reviews distribution assumptions and describes a weighted least squares procedure for addressing non-Gaussianity. Recent abstracts indicate that a Rician noise model is more accurate than Gaussian estimation (e.g., [1]).…”
Section: Introductionmentioning
confidence: 99%